Perceived COVID-19 anxiety, fear and depression levels among university students during the decreased restrictions of COVID-19 pandemic - Baş, Kazim (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. The COVID-19 pandemic has negatively impacted human life. It is observed that a significant group affected by this situation are university students. Evaluating the psychological states of students during the transition to normal life from the pandemic period is important. This study was conducted to examine the perceived levels of COVID-19 anxiety, fear, and depression among university students during the descreased restrictions of the COVID-19 pandemic. Material and methods. This cross-sectional study was conducted with 1170 university students. The data were collected using “the Introductory Information Form, the Fear of COVID-19 Scale, the Coronavirus Anxiety Scale – Short Form, and the Depression Scale. Results. It was observed that there was a difference between gender, class, education level, income level, having had COVID-19, and having a deceased relative due to COVID-19 and perceived COVID-19 anxiety and fear and depression levels among university students (p<0.05). Conclusion. During the COVID-19 pandemic, although restrictions have been lifted, students still experience moderate levels of COVID-19 anxiety, fear, and depression. Therefore, considering the factors that affect university students’ mental state, there is a need for services that support students’ mental well-being.
Written permissions were obtained from the Non-Interventional Research Ethics Committee of a University (decision no. 03 dated January 28, 2022 and letter no. 42594 dated February 7, 2022).
Keywords: anxiety; depression; fear; pandemic; university students